PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENGUKUR KINERJA MANAJER PADA CV. USAHA SEMESTA - RIO TAMBUNAN; IRWAN DJANAHAR; M. LIAN DALIMUNTHE (JURNAL ILMIAH MAKSITEK, 2020)
The purpose of this study is to formulate a strategy for applying accounting that is more effective and efficient in order toimprove manager performance. The data collected is analyzed based on financial ratios and SWOT. The results showedthat, the performance of managers in the period 2008-2010 were respectively ROI values in 2008 amounted to 44%, in 2009amounted to 36% and in 2010 amounted to 45%. The manager's performance when measured from the application ofresponsibility accounting varies from 2008-2009 to a decrease, while in 2009-2010 there was an increase. The steps in theimplementation of the responsibility accounting strategy are: 1) determining the area of responsibility of the managerresponsible; 2) determining the performance of the budget used to measure the performance of the responsibility centermanagers; and 3) actual performance measurement.